Analysis of Operational Audit and Return Accounting Information System on Sales Turnover on CV. Irama Houseware - Karsima Delila Br Keliat; Fhikry Ahmad H Siregar; Etty Harya Ningsi (Primanomics : Jurnal Ekonomi & Bisnis, 2025)
This study aims to analyze the influence of operational audit and return accounting information system  on sales turnover in CV. Rhythm Houseware. Operational audits focus on evaluating operational efficiency and effectiveness, while return accounting information systems help in managing  accurate return data  . The research method used was a quantitative approach by collecting data through questionnaires to 35 respondents working at CV. Rhythm Houseware. Data analysis was carried out using multiple regression with the help of SPSS version 29. The results of the analysis show that the independent variables, operational audit and return accounting information system, have a strong correlation with the dependent variable, namely sales turnover, with a determination coefficient (R2) value of 0.826 or 82.6%. This indicates that 82.6% of the variation in sales turnover can be explained by this variable, while the remaining 17.4% is influenced by other factors outside the model. The results of the partial test (t-test) showed that the operational audit variable had a coefficient of 0.029 with a significance value of 0.816 which means it was not significant to sales turnover. On the other hand, the variable of the retun  accounting information system showed a coefficient of 0.761 with a significance of <0.001 which showed a significant positive influence on sales turnover. Thus, the return accounting information system  plays an important role in increasing sales turnover. The results of the simultaneous test (test f) showed that the two variables, operational audit and return accounting information system, together had a significant effect on sales turnover, with an F-calculated value of 75.745 and a significance of <0.001. Thus, operational audit does not have a significant influence on sales turnover, while the return accounting information system  has a significant effect. A  more effective implementation of the return accounting information system  can improve return data management, improve operational audits, and ultimately increase sales turnover in CV. Rhythm Houseware. The recommendation for the Company is to continue to strengthen these two factors to maintain the stability of sales turnover.